Practical Site Reliability Engineering : Automate the process of designing, developing, and delivering highly reliable apps and services with SRE /: Automate the process of designing, developing, and delivering highly reliable apps and services with SRE. (2018) - Chelliah, Pethuru Raj; Naithani, Shreyash; Singh, Shailender
No abstract available